PENGARUH STRES KERJA DAN IKLIM ORGANISASI TERHADAP TURNOVER INTENTION PADA PEGAWAI DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN LINGKUNGAN HIDUP KOTA SIBOLGA - Simanjuntak, Lisa Endryani; Sinaga, Nelly Azwarni; Tanjung, Mansur (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of Work Stress and Organizational Climate on Turnover Intention in Sibolga City Housing, Settlement and Environment Office employees, either partially or simultaneously. The sample in this study were 45 respondents at the Sibolga City Housing, Settlement and Environment Service Office. The multiple linear regression method of determining the sample in this study shows that partially this relationship is a linear and significant relationship. The influence of Work Stress and Organizational Climate on Turnover Intention at the Office of Housing, Residential Areas and the Environment in Sibolga City, is indicated by a coefficient of determination of 0.20. This shows that 20% of employee Turnover Intention is influenced by Work Stress and Organizational Climate and the remaining 0.80 or 80% is influenced by other variables not used in this study. The results of the research conducted, that Work Stress and Organizational Climate have a simultaneous relationship with Employee Turnover Intention, which means that the two variables have the same position in the influence of Turnover Intention on employees in the Sibolga City Housing, Settlement and Environmental Office. The writer's hypothesis is that it is known that the results of the F test have a simultaneous effect which based on the output it is known that the significant value for the effect of X1 and X2 simultaneously on Y is 0.009 <0.05 and the calculated F value is 5.284 > 2.18, so it can be concluded that H3 is accepted which means there is an effect of X1 and X2 simultaneously on Y.